Barriers to Contraceptive Access in Disaster Situations: A Systematic Review of Health System Preparedness and Socio-Cultural Challenges - Alfiana Ainun Nisa; Efa Nugroho; Ayu Istiada; Annisa Novanda Maharani Utami; Dwi Yunanto Hermawan; Heny Widyaningrum (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: This study examines barriers to access to contraceptive services in disaster situations in the context of reproductive health system preparedness and socio-cultural challenges. According to the United Nations Population Fund (UNFPA) report in 2022, 51.3% of married women have not used contraceptives, and around 11.3% of family planning needs are unmet. In disaster situations, these problems are further complicated by limited infrastructure, unequal distribution of services, and weak health system preparedness. The inability to meet contraceptive needs can increase the risk of unplanned pregnancies and reproductive health complications, exacerbating the impact of disasters on women and other vulnerable groups. This study aims to fill this research gap by providing a comprehensive review of the factors that hinder access to contraceptive services during disasters and proposing policy-based strategies to improve health system preparedness in emergency response. Methods: This study is a systematic review that collects several studies according to PRISMA guidelines. Using relevant keywords, studies were obtained from PubMed, Science Direct, and Scopus databases. Studies were collected from June to July 2024. Results: Key findings suggest that socio-cultural, religious, and economic factors influence barriers to contraceptive access during disasters. Limited knowledge, social stigma, cultural and religious norms, and financial instability contribute to low utilization of contraceptive services. In addition, disruptions due to disasters and the COVID-19 pandemic limit community mobility, hinder access to health facilities and exacerbate service gaps for vulnerable groups, including refugees and migrants. Conclusion: This study highlights the importance of a human rights-based approach in ensuring the accessibility of contraceptive services in crisis situations. Policy implications include strengthening reproductive health systems in emergency response, reducing stigma through community education, and increasing stakeholder engagement in ensuring equitable distribution of services. The results of this study contribute to the global discourse on reproductive health rights in disaster contexts and provide a basis for innovative strategies to expand access to services in conflict-affected or remote areas.